"It's Not Over When It's Over"―Post-Decision Arrangements and Empirical Legitimacy. (1st July 2021) - de Fine Licht, Jenny; Agerberg, Mattias; Esaiasson, Peter
Abstract: A chronic problem for democratic governments is generating legitimacy for policy decisions that go against substantial groups of citizens' legitimate interests. The primary means of achieving this aim involve the arrangements through which policy decisions are made. Whereas research in the field has tended to focus on the arrangements leading up to a decision, this paper draws attention to developments after a formal policy decision has been made. We theorize that the formal decision constitutes a focal event that motivates affected individuals to update their beliefs about the decision. We identify four types of potential legitimacy-enhancing post-decision arrangements: how the decision is announced; how it is publicly explained; whether the process allows for post-decision voice; and whether decision-makers take actions to mitigate its negative consequences. The results from two survey experiments with large samples of Swedish adults addressing the case of school closures suggest that post-decision procedures have legitimacy-enhancing potential and that this effect is not dependent on the pre-decision process.